In search of lost reason: Ramsey, Keynes, and the intellectualism debate - Soroush Marouzi (Duke University, Center for the History of Political Economy (CHOPE), 2024)
The outbreak of the Great War facilitated a shift in the dominant view of human nature within the Bloomsbury-Cambridge intelligentsia, steering it away from an optimistic view toward a pessimistic one. The conceptualization of human reason and rationality, however, remained intact by the war. Frank Ramsey and John Maynard Keynes produced some of their most notable works within this evolving intellectual context. The two Cambridge philosopher-economists followed the interwar orthodoxy by adopting its description of human nature. But they departed from that orthodoxy by revising its underlying conceptual commitment concerning what constitutes human reason and rationality. Ramsey and Keynes developed their ideas in tandem. They both argued for the pragmatist idea that our normative theory of human life ought to be sensitive to what we can ask from human nature. Ramsey made that argument in his philosophy. Keynes made it in his economics.
Keywords: 330